Everolimus is associated with a reduced incidence of cytomegalovirus infection following de novo cardiac transplantation. Issue 2 (26th September 2012) - Kobashigawa, J.; Ross, H.; Bara, C.; Delgado, J.F.; Dengler, T.; Lehmkuhl, H.B.; Wang, S.‐S.; Dong, G.; Witte, S.; Junge, G.; Potena, L.
Abstract Background Cytomegalovirus (CMV) causes several complications following cardiac transplantation including cardiac allograft vasculopathy. Previous studies suggested that immunosuppressive treatment based on everolimus might reduce CMV infection. Aiming to better characterize the action of everolimus on CMV and its interplay with patient/recipient serology and anti‐CMV prophylaxis, we analyzed data from 3 large randomized studies comparing various everolimus regimens with azathioprine (AZA)‐ and mycophenolate mofetil (MMF)‐based regimens. Methods CMV data were analyzed from 1009 patients in 3 trials of de novo cardiac transplant recipients who were randomized to everolimus 1.5 mg/day, everolimus 3 mg/day, or AZA 1–3 mg/kg/day, plus standard‐dose (SD) cyclosporine (CsA; study B253, n = 634); everolimus 1.5 mg/day plus SD‐ or reduced‐dose (RD)‐CsA (study A2403, n = 199); and everolimus 1.5 mg/day plus RD‐CsA or MMF plus SD‐CsA (study A2411, n = 176). Results In study B253, patients allocated to everolimus experienced almost a 70% reduction in odds of experiencing CMV infection compared with AZA (P < 0.001). In study A2403, CMV infection was low in both everolimus arms, irrespective of CsA dosing, and in study A2411, patients allocated to everolimus experienced an 80% reduction in odds of experiencing CMV infection, compared with MMF (P < 0.001). CMV syndrome/disease was rare and less frequent in everolimus‐treated patients. Subgroup analyses showed that the benefit everolimus provides, in terms of CMV events, is retained in CMV‐naïve recipients and is independent of anti‐CMV prophylaxis or preemptive approaches. Conclusions Everolimus is associated with a lower incidence of CMV infection compared with AZA and MMF, which combined with its immunosuppressive efficacy and antiproliferative effects may positively impact long‐term outcomes.